2013
DOI: 10.1007/s00705-013-1849-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of curcumin on dengue virus type 2-infected cells in vitro

Abstract: Curcumin, a traditional Chinese and Indian treatment for many diseases, has recently been found to alter the in vitro infection processes of various viruses, including hepatitis C virus, human immunodeficiency virus, coxsackievirus, and Japanese encephalitis virus. The present study evaluated the cellular effects of curcumin in an in vitro (cellular) infection model of dengue virus. Within a dose range of 10 to 30 μM and a treatment period of 24 hours, the cytotoxicity of curcumin was low, as determined by MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 26 publications
3
61
0
Order By: Relevance
“…The natural phytochemicals found in Tinospora cordifolia are known to show antiviral activity for many viral infections [46][47][48]. Curcumin, a component of turmeric (Curcuma longa) has been described to have several functions in preventing or treating diseases, including cancers and viral infections [49]. It has also been demonstrated that curcumin is an antiviral compound, with activity against diverse viruses such as dengue virus (serotype 2) [50], herpes simplex virus [51], human immunodeficiency virus [52], Zika and Chikungunya [53] among others.…”
Section: Introductionmentioning
confidence: 99%
“…The natural phytochemicals found in Tinospora cordifolia are known to show antiviral activity for many viral infections [46][47][48]. Curcumin, a component of turmeric (Curcuma longa) has been described to have several functions in preventing or treating diseases, including cancers and viral infections [49]. It has also been demonstrated that curcumin is an antiviral compound, with activity against diverse viruses such as dengue virus (serotype 2) [50], herpes simplex virus [51], human immunodeficiency virus [52], Zika and Chikungunya [53] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compounds with no specific target have also been reported, which have been shown to affect the viral replication cycle, such as curcumin, a natural compound with several inhibitory effects in in vitro dengue type 2 virus-infected cells [19]. However, until now no antivirals compounds have been approved to treat diseases caused by flaviviruses [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, curcumin, one of the major components of C. longa , has shown inhibition of HIV-1 and HIV-2 proteases [59] and in-vitro infectivity of dengue virus type 2 [60]. García Ariza and co-workers have suggested that dengue virus RNA-dependent RNA polymerase inhibition by curcumin, based on molecular docking studies, may be responsible for the anti-dengue activity of curcumin [61].…”
Section: Resultsmentioning
confidence: 99%